Adherence to colorectal cancer screening: Four rounds of faecal immunochemical test-based screening - Van Der Vlugt, M.; Grobbee, E.; Bossuyt, P.; Bongers, E.; Spijker, W.; Kuipers, E.; Lansdorp_Vogelaar, Iris; Essink-Bot, M.; Spaander, M.; Dekker, E. (Nature Publishing Group, 2017)
Background:The effectiveness of faecal immunochemical test (FIT)-based screening programs is highly dependent on consistent participation over multiple rounds. We evaluated adherence to FIT screening over four rounds and aimed to identify determinants of participation behaviour.Methods:A total of 23 339 randomly selected asymptomatic persons aged 50-74 years were invited for biennial FIT-based colorectal cancer screening between 2006 and 2014. All were invited for every consecutive round, except for those who had moved out of the area, passed the upper age limit, or had tested positive in a previous screening round. A reminder letter was sent to non-responders. We calculated participation rates per round, response rates to a reminder letter, and differences in participation between subgroups defined by age, sex, and socioeconomic status (SES).Results:Over the four rounds, participation rates increased significantly, from 60% (95% CI 60-61), 60% (95% CI 59-60), 62% (95% CI 61-63) to 63% (95% CI 62-64; P for trend<0.001) with significantly higher participation rates in women in all rounds (P<0.001). Of the 17 312 invitees eligible for at least two rounds of FIT screening, 12 455 (72%) participated at least once, whereas 4857 (28%) never participated; 8271 (48%) attended all rounds when eligible. Consistent participation was associated with older age, female sex, and higher SES. Offering a reminder letter after the initial invite in the first round increased uptake with 12%; in subsequent screening rounds this resulted in an additional uptake of up to 10%.Conclusions:In four rounds of a pilot biennial FIT-screening program, we observed a consistently high and increasing participation rate, whereas sending reminders remain effective. The substantial proportion of inconsistent participants suggests the existence of incidental barriers to participation, which, if possible, should be identified and removed.